2015
DOI: 10.3892/ijmm.2015.2111
|View full text |Cite
|
Sign up to set email alerts
|

The proliferative effects of Pyropia yezoensis peptide on IEC-6 cells are mediated through the epidermal growth factor receptor signaling pathway

Abstract: For a number of years, seaweed has been used as a functional food in Asian countries, particularly in Korea, Japan and China. Pyropia yezoensis is a marine red alga that has potentially beneficial biological activities. In this study, we examined the mechanisms through which a Pyropia yezoensis peptide [PYP1 (1–20)] induces the proliferation of IEC-6 cells, a rat intestinal epithelial cell line, and the involvement of the epidermal growth factor receptor (EGFR) signaling pathway. First, cell viability assay re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Food derived bioactive peptides have been shown to modulate intestinal epithelial cell differentiation and cytokine production [ 76 ]. Among these, a bioactive peptide derived from Porphyra yezoensis , termed PY-PE or PYP1, whose sequence is A-L-E-G-G-K-S-S-G-G-G-E-A-T-R-D-P-E-P-T, has been shown to induce the proliferation of IEC-6 cells, a rat intestinal epithelial cell line [ 77 , 78 ]. The stimulation of two different molecular signaling pathways has been found to be involved in this effect.…”
Section: Red Seaweeds and Intestinal Mucosal Barrier Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food derived bioactive peptides have been shown to modulate intestinal epithelial cell differentiation and cytokine production [ 76 ]. Among these, a bioactive peptide derived from Porphyra yezoensis , termed PY-PE or PYP1, whose sequence is A-L-E-G-G-K-S-S-G-G-G-E-A-T-R-D-P-E-P-T, has been shown to induce the proliferation of IEC-6 cells, a rat intestinal epithelial cell line [ 77 , 78 ]. The stimulation of two different molecular signaling pathways has been found to be involved in this effect.…”
Section: Red Seaweeds and Intestinal Mucosal Barrier Functionmentioning
confidence: 99%
“…Epidermal growth factor (EGF) is an important factor in the regulation of MBF, as it stimulates epithelial cell growth, proliferation and differentiation by binding to its receptor (EGFR) and the subsequent activation of several signaling pathways. PY-PE has been shown to increase the expression of EGFR and the adaptor molecules Shc, growth factor receptor bound 2 (Grb2) and Son of Sevenless (SOS), and to activate the Ras/Raf/mitogen activated protein kinase (MAPK)-ERK kinase (MEK)/extracellular signal-regulated kinases (ERK) pathway (Ras/Raf/MEK/ERK) [ 77 ]. The final effect is the recruitment of cells into G1 phase, with an increased expression of cyclins D and E, cyclin dependent kinase (CDK) 2, 4 and 6, and a decrease in the expression of cell cycle inhibitors p21 and p27.…”
Section: Red Seaweeds and Intestinal Mucosal Barrier Functionmentioning
confidence: 99%
“…Pyropia yezoensis, a species of marine algae, has long been consumed in Korea, Japan and China. It has a range of biological activities, including cell proliferation (21), antioxidation (22) and antiinflammatory effects (23). In the present study, the in vivo protective effect of P. yezoensis on chronic ethanol consumption-induced liver injury was investigated in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only one study using a particular PYP peptide has reported its regulation of multiple cell growth-related signals in MCF-7 cells ( 25 ). PYP has also been shown to stimulate the proliferation of IEC-6 normal intestinal epithelial cells and is associated with the insulin-like growth factor I (IGF-IR) and epidermal growth factor receptor (EGFR) signaling pathways ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%